Measuring Accreditation Activity and Progress: Findings from a Survey of Indiana Local Health Departments, 2013. (September 2015) - Meyerson, Beth E.; Barnes, Priscilla R.; King, Jerry; Degi, Lindsey S.; Halverson, Paul K.; Polmanski, Haley F.
A 2013 survey of Indiana local health departments (LHDs) measured accreditation activity and progress. Reported activities were categorized using the Public Health Accreditation Board's (PHAB's) accreditation steps as a guiding framework and matched with selected sociodemographic, organizational, and technical assistance variables. Findings indicated that 42 (59.2%) of responding Indiana LHDs reported pursuing accreditation. Of LHDs pursuing accreditation, 21 were at the initial introductory step, 18 were at the prerequisite step, one reported submitting an application to PHAB, and two reported no activity, yet intent to pursue accreditation. Reported receipt of technical assistance was associated with accreditation progress ( p =0.01) and, specifically, with being at the prerequisite step. Facilitating the pursuit of LHD accreditation in states with low public health investment is possible with targeted accreditation resources. Finding meaningful measures of accreditation progress will help advance the study of factors associated with LHD accreditation on a broad scale and for the long term.